Modern marvels. [videorecording] - Nash, Bruce M.; Fulkerson, Lee; Thomas, Guy; History Channel (Television network); Arts and Entertainment Network; New Video Group ([New York, NY] : Distributed by New Video)
In Hollywood, they are home to killer mummies and booby traps. Now, separate fact from fantasy with this tour of the Egyptian Pyramids, which traces the rise of one of the ultimate accomplishments of the Ancient World